2000
DOI: 10.1007/s004250050686
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of guaiacyl to syringyl moieties on the cinnamyl alcohol pathway during the biosynthesis of lignin in angiosperms

Abstract: Aglycons derived from 4-O-beta-D-glucosides of both caffeyl and 5-hydroxyconiferyl alcohols were incorporated into guaiacyl (G) and syringyl (S) units in the lignin of newly formed xylem of several angiosperms. It is likely that these aglycons enter the cinnamyl alcohol pathway as intermediates in the introduction of methoxyl groups onto aromatic rings, and serve as precursors for the biosynthesis of lignin. The S/G ratio in this pathway was coincident with the ratio in the cell wall lignin of each tree. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 20 publications
5
22
0
Order By: Relevance
“…This secondary 3-Omethylation activity likely accounts for the slight decreases in levels of G-lignin in OMT1-deficient transgenic ryegrass (Tu et al, 2010). Again, this observed activity of Lp OMT1 is in agreement with the properties of COMTs from other plant species (Maury et al, 1999;Dixon et al, 2001;Parvathi et al, 2001;Do et al, 2007;Ma and Xu, 2008;Guillaumie et al, 2008): in Arabidopsis thaliana, the retained ability to synthesize both G-and S-lignin in CCoAOMT knockouts but not CCoAOMT/COMT double knockouts (Do et al, 2007); and radiochemical labeling studies that demonstrate the incorporation of exogenously supplied caffeoyl alcohol and caffeoyl aldehyde ultimately into both G-and S-subunits of angiosperm lignin (Matsui et al, 2000). Finally, the permissiveness in substrate acceptance by the COMTs intriguingly suggests that developmental adjustments in the in vivo levels of monolignol precursors may be sufficient to modulate the biosynthesis and availability of specific monolignols that are then incorporated through polymerization into lignin.…”
Section: Insight Into the Substrate Preferences Of Comtssupporting
confidence: 81%
“…This secondary 3-Omethylation activity likely accounts for the slight decreases in levels of G-lignin in OMT1-deficient transgenic ryegrass (Tu et al, 2010). Again, this observed activity of Lp OMT1 is in agreement with the properties of COMTs from other plant species (Maury et al, 1999;Dixon et al, 2001;Parvathi et al, 2001;Do et al, 2007;Ma and Xu, 2008;Guillaumie et al, 2008): in Arabidopsis thaliana, the retained ability to synthesize both G-and S-lignin in CCoAOMT knockouts but not CCoAOMT/COMT double knockouts (Do et al, 2007); and radiochemical labeling studies that demonstrate the incorporation of exogenously supplied caffeoyl alcohol and caffeoyl aldehyde ultimately into both G-and S-subunits of angiosperm lignin (Matsui et al, 2000). Finally, the permissiveness in substrate acceptance by the COMTs intriguingly suggests that developmental adjustments in the in vivo levels of monolignol precursors may be sufficient to modulate the biosynthesis and availability of specific monolignols that are then incorporated through polymerization into lignin.…”
Section: Insight Into the Substrate Preferences Of Comtssupporting
confidence: 81%
“…Consistent with this, alfalfa COMT has a strong kinetic preference for both of these caffeoyl substrates , and radiochemical labeling studies demonstrated the incorporation of caffeoyl alcohol and caffeoyl aldehyde into both G and S subunits (Matsui et al, 2000). Recombinant COMT protein from wheat showed the highest level of catalytic activity toward both caffeoyl aldehyde and 5-hydroxyconiferaldehyde (Ma and Xu, 2008).…”
Section: Discussion Functional Analysis Of the Omt1 Gene In Perennialsupporting
confidence: 54%
“…Lipases, oxidases, and esterases along with LiP that may enter the cell wall and break the lignin barrier (Zeng et al 2014). Glucosides were employed as effective precursors in lignin biosynthesis (Matsui et al 2000).…”
Section: Lignin Degradationmentioning
confidence: 99%